Copper-Catalyzed Oxidative Cyanation of Aryl Halides with Nitriles Involving Carbon–Carbon Cleavage - Song, Ren-Jie; Wu, Ji-Cheng; Liu, Yu; Deng, Guo-Bo; Wu, Cui-Yan; Wei, Wen-Ting; Li, Jin-Heng (Synlett, 2012)
A novel, general route for the synthesis of aromatic nitriles is presented that proceeds through Cu(OAc)2-catalyzed oxidative cyanation of aryl halides using commercially available nitriles as the cyanide sources and Ag2O/air as the oxidizing agent. It is noteworthy that this work provides a new example of using acetonitrile as the cyanide source for aromatic nitrile synthesis through a Cu-catalyzed oxidative C–C bond cleavage and cyanation process.
Keywords: copper; oxidation; cyanation; aryl halides; nitriles